Biophysical assessment of the plant biodiversity of Northern Negros Natural Park, Negros Island, Philippines (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Jr Dechimo AA, Jr Buot IE. 2023. Biophysical assessment of the plant biodiversity of Northern Negros Natural Park, Negros Island, Philippines. Biodiversitas 24: 583-602. Data sets on plant bioresources in Northern Negros Natural Park are critical in planning for conservation management and strategies. This study aimed to (i) conduct a survey of plant species in NNNP and determine their conservation status, (ii) assess the species diversity pattern and vegetation structures, (iii) establish altitudinal zones, and (iv) analyze the environmental factors affecting species distribution. Standard vegetation analysis and secondary data were utilized in the data collection process. Results showed 242 species, 72 families of 78 tree species, 90 shrubs and small trees, and 37 epiphytes. About 112 species are threatened, 35 of which are Philippine endemics. Two altitudinal zones were identified using the cluster analysis: Zone I (643 to 1,256 m asl.), dominated by Crypteronia paniculata, Acer laurinum, Weinmannia hutchinsonii, and Syzygiumsp.; and Zone II (1421 to 1470 m asl.) dominated by Dacrydium cf. beccarii. Zone I was further subdivided into three clusters: Zone IA (643 to 985 m asl.), Zone IB (908 to 913 m asl.), and Zone IC (822 to 1,182 m asl.). Canonical correspondence analysis illustrated that environmental factors (N, Altitude, and human disturbance) influenced the zonation of vegetation or species abundance. These results are important in understanding the landscape and crafting strategic interventions and management plans for conservation.